2013
DOI: 10.1158/0008-5472.sabcs13-p4-01-05
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P4-01-05: 3’-deoxy-3’-[18F]fluoro-thymidine (18F-FLT) positron emission tomography (PET): An accurate and effective tool for assessing tumor response in breast cancer

Abstract: Objectives : A French multicenter study was promoted by the national French cancer federation (Unicancer R&D) to assess the potential of [18F]FLT (positron emission tomography (PET) biomarker of proliferation)to manage breast cancer neoadjuvant chemotherapy (NAC). The main objective was to compare changes in tumor [18F]FLT uptake to histopathological changes induced by NAC, assuming an arrest of tumor growth related to the effectiveness of NAC. Methods : 97 patients (age 48.6 +/- 10.2 y.) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Small, single-center preliminary studies indicated good predictive value for response (1114), whereas others did not (12,1517). Our multicenter study suggested some utility for 18 F-FLT as an early predictor of response, but preliminary reports of other multicenter trials did not find a predictive value for 18 F-FLT (25).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Small, single-center preliminary studies indicated good predictive value for response (1114), whereas others did not (12,1517). Our multicenter study suggested some utility for 18 F-FLT as an early predictor of response, but preliminary reports of other multicenter trials did not find a predictive value for 18 F-FLT (25).…”
Section: Discussionmentioning
confidence: 96%
“…18 F-FLT is a substrate for thymidine kinase-1, and the accumulation of 18 F-FLT in tumors provides a quantitative measure of cell proliferation through the relationship between thymidine kinase-1 expression and cell cycle regulation (69). Several prior single-center studies have demonstrated that changes in breast cancer tumor proliferation assessed by 18 F-FLT PET/CT early after initiating chemotherapy predict tumor response with good sensitivity; however, the results of these studies were variable and none of the prior studies investigated the potential for predicting pCR to NAC (1017). In the present multicenter study, our objective was to correlate changes measured by 18 F-FLT in the primary tumor early during NAC with pCR in locally advanced breast cancer patients.…”
mentioning
confidence: 99%